2022
DOI: 10.1007/s00894-022-05395-2
|View full text |Cite
|
Sign up to set email alerts
|

Cancer regulator EGFR-ErbB4 heterodimer is stabilized through glycans at the dimeric interface

Abstract: The ErbB family of tyrosine kinase receptors is composed of four homologous members, including EGFR (ErbB1/HER1), ErbB2 (HER2), ErbB3 (HER3), and ErbB4 (HER4). Since the ErbB proteins play vital roles in various developmental processes, their mutation or overexpression leads to severe abnormalities such as cancer. The general mechanism of ErbB receptors activity is binding to growth factors via their extracellular domain followed by tyrosine phosphorylation intracellularly. Yet the EGFR and ErbB4 are the only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 59 publications
1
3
0
Order By: Relevance
“…To our knowledge, the cryo-EM maps of HER4 homodimers and HER2/HER4 heterodimers offer the first glimpse into extensive glycan-mediated contacts in an active HER receptor dimer. The observed interactions might explain some of the stabilizing effects of HER receptor glycosylation previously suggested ( Motamedi et al, 2022 ). We identified glycans in both HER2 and HER4 that directly connect their domains I and II and the HER4-specific interdomain glycan connections between domains II and IV.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…To our knowledge, the cryo-EM maps of HER4 homodimers and HER2/HER4 heterodimers offer the first glimpse into extensive glycan-mediated contacts in an active HER receptor dimer. The observed interactions might explain some of the stabilizing effects of HER receptor glycosylation previously suggested ( Motamedi et al, 2022 ). We identified glycans in both HER2 and HER4 that directly connect their domains I and II and the HER4-specific interdomain glycan connections between domains II and IV.…”
Section: Discussionsupporting
confidence: 55%
“…In recent years several studies of the effects of HER receptor glycosylation on their structure and signaling have been conducted using molecular dynamics (MD) generating models on how glycans contribute to receptor stability and its interactions with the membrane ( Taylor et al, 2017 ; Arkhipov et al, 2013 ; Kaszuba et al, 2015 ; Azimzadeh Irani et al, 2017 ). Most recently, MD simulations conducted on the HER4/EGFR heterodimer models have suggested that the glycans present on HER4 N358 and N548, as well as EGFR N361 (which is equivalent to HER4 N358), form a connection in the dimerization interface that effectively stabilizes the heterodimer ( Motamedi et al, 2022 ). Our current study provides the first direct experimental evidence that these glycan interactions are operative at the level of HER4 homodimers.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the cryo-EM maps of HER4 homodimers and HER2/HER4 heterodimers offer the first glimpse into extensive glycan-mediated contacts in an active HER receptor dimer. The observed interactions might explain some of the stabilizing effects of HER receptor glycosylation previously suggested [62]. We identified glycans in both HER2 and HER4 that directly connect their domains I and II and the HER4-specific interdomain glycan connections between domains II and IV.…”
Section: Discussionmentioning
confidence: 65%
“…In recent years several studies of the effects of HER receptor glycosylation on their structure and signaling has been conducted using molecular dynamics (MD) generating models on how glycans contribute to receptor stability and its interactions with the membrane [63][64][65][66]. Most recently, MD simulations conducted on the HER4/EGFR heterodimer models have suggested that the glycans present on HER4 N358 and N548, as well as EGFR N361 (which is equivalent to HER4 N358), form a connection in the dimerization interface that effectively stabilizes the heterodimer [62]. Our current study provides first direct experimental evidence that these glycan interactions are operative at the level of HER4 homodimers.…”
Section: Biased Agonismmentioning
confidence: 99%